The Role of Akhlak Intelligence: Mediation Between Self-Efficacy and Entrepreneurial Orientation - Junusi, Rahman El (Journal of Digital Marketing and Halal Industry, 2021)
This study attempts to fill the gap in the literature between self-efficacy and entrepreneurial orientation (EO). The purpose of this study was to determine the effect of self-efficacy and EO mediated by moral intelligence. Data collection was carried out from a population of 17,603 Muslim entrepreneurs in the city of Semarang who are engaged in the Micro, Small, and Medium Enterprises (MSMEs) sector. The data collected from the online survey was applied to structural equation modeling (SEM). From this study, it was found that self-efficacy has a significant effect on EO and moral intelligence, while moral intelligence affects EO. This study contributes to the literature on the role of self-efficacy and moral intelligence in increasing EO. The originality of this study is to offer the concept of moral intelligence which plays a central role in the relationship between self-efficacy and EO. Thus, no studies have investigated this causality.